2016
DOI: 10.3389/fmicb.2016.00727
|View full text |Cite
|
Sign up to set email alerts
|

Drying-Rewetting and Flooding Impact Denitrifier Activity Rather than Community Structure in a Moderately Acidic Fen

Abstract: Wetlands represent sources or sinks of the greenhouse gas nitrous oxide (N2O). The acidic fen Schlöppnerbrunnen emits denitrification derived N2O and is also capable of N2O consumption. Global warming is predicted to cause more extreme weather events in future years, including prolonged drought periods as well as heavy rainfall events, which may result in flooding. Thus, the effects of prolonged drought and flooding events on the abundance, community composition, and activity of fen denitrifiers were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
(130 reference statements)
1
9
1
Order By: Relevance
“…The denitrifying bacterial communities appeared to be even more resistant to disturbance by the changing water level than the total bacterial communities, with no significant differences. This resistance is consistent with prior studies in other environments, such as acidic fens (Palmer et al, 2016) and is likely due to the metabolic versatility of most denitrifying bacteria. The resistance of these communities to the disturbance of changing water levels is an advantage for their application in denitrifying bioreactors, where water level fluctuations are frequent.…”
Section: Discussionsupporting
confidence: 91%
“…The denitrifying bacterial communities appeared to be even more resistant to disturbance by the changing water level than the total bacterial communities, with no significant differences. This resistance is consistent with prior studies in other environments, such as acidic fens (Palmer et al, 2016) and is likely due to the metabolic versatility of most denitrifying bacteria. The resistance of these communities to the disturbance of changing water levels is an advantage for their application in denitrifying bioreactors, where water level fluctuations are frequent.…”
Section: Discussionsupporting
confidence: 91%
“…This correlation suggests differential response to altered environmental conditions against the background of a community which remained unaltered. Palmer et al ( 2016 ), for instance, observed differential transcriptional activation of denitrifiers in response to drying-rewetting and flooding. Hence, future studies should explore in more detail how elevated CO 2 in conjunction with massive N inputs during fertilization impact microbial communities in the soil and whether this leads to a short-term activation of microbial groups involved in N-cycling and hence higher production of N 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…One such management option is drying–rewetting (DRW) cycles. In the soil literature, a number of studies investigated the effect of DRW cycles on the rates of soil metabolic processes (Beare et al, 2009; Borken and Matzner, 2009; Miller et al, 2005; Ruser et al, 2006; Palmer et al, 2016; Xiang et al, 2008). Drying–rewetting cycles in soils have been linked to increased nitrous oxide (N 2 O) production (Ruser et al, 2006), increased C and N leaching (Miller et al, 2005), and changes in microbial and fungal communities (Gordon et al, 2008).…”
mentioning
confidence: 99%